Polymorphism of HLA and Susceptibility of Breast Cancer - Aboulaghras, Sara; Khalid, Asaad; Makeen, Hafiz A; Alhazmi, Hassan A; Albratty, Mohammed; Mohan, Syam; Goh, Bey Hing *; Yeo, Chien Ing *; Tan, Yee Seng *; Bouyahya, Abdelhakim (IMR Press, 2024)
Breast cancer (BC) is the second most common malignancy in the world. Numerous studies have demonstrated the association between human leukocyte antigen (HLA) and cancer. The occurrence and development of BC are closely linked to genetic factors. Human leukocyte antigens G and E (HLA-G and HLA-E) are non-classical major histocompatibility complex (MHC) class I molecules. These molecules play an important role in immune surveillance by inhibiting the cytotoxic and natural killer T cells responsible for immune escape. The expression of HLA-G and HLA-E has been associated with several diseases, including tumors. The HLA system plays a key role in the escape of tumor cells from immune surveillance. This review aims to determine the correlation between BC susceptibility and HLA markers specific HLA alleles such as HLA-B07, HLA-DRB111, HLA-DRB113, and HLA-DRB115 are associated with an increased risk of developing BC. Furthermore, HLA-G mutations have been attributed to an elevated likelihood of metastasis in BC patients. Understanding the complex associations between the HLA system and BC development is critical for developing novel cancer prevention, detection, and treatment strategies. This review emphasizes the importance of analyzing HLA polymorphisms in the management of BC patients, as well as the urgent need for further research in this area.